Uzbekistan and Turkey: Towards an eternal fraternity - Kamoliddin Sharipovich Hasanov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article intends to thoroughly analyze the beginning of relations between Uzbekistan and Turkey and their historical significance